2011
DOI: 10.1002/zoo.20419
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Milestones, Behavior and Growth Rate of Sumatran Rhinoceros (Dicerorhinus sumatrensis) Calves Born and Bred in Captivity

Abstract: The birth of Sumatran rhino calves at the Cincinnati Zoo and Botanical Garden offered a unique opportunity to study early development and cow-calf behavior in this elusive, critically endangered species. Study goals were to: (1) record developmental milestones of newborn calves; (2) characterize cow and calf behavior during the first year following birth; (3) compare trends in the behavioral development of a male vs. female calf; and (4) record weight gain and footprint size throughout the first year. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…In line with most studies on ungulates (Gauthier & Barrette, ; Byers & Moodie, ; Green, ; Lent, ; Birgersson & Ekvall, ; Alley, Fordham & Minot, ; Špinka & Algers, ; Das et al ., ; Dalezsczyk, ), we found that suckling bout duration and frequency decreased with increasing age of the foal in all three observed zebra species. However, in several ungulate species (cattle, impala Aepyceros melampus , Sumatran rhinoceros Dicerorhinus sumatrensis ), suckling bout duration is not affected by the age of the young (Lewandrowski & Hurnik, ; Mooring & Rubin, ; Plair, Reinhart & Roth, ) or even increased with an increasing age of the young (eland Taurotragus oryx ; Underwood, ; common hippopotamus Hippopotamus amphibius ; Pluháček & Bartošová, ). Therefore, we suggest that suckling bout duration seems to be better indicator of offspring needs than suckling frequency.…”
Section: Discussionmentioning
confidence: 99%
“…In line with most studies on ungulates (Gauthier & Barrette, ; Byers & Moodie, ; Green, ; Lent, ; Birgersson & Ekvall, ; Alley, Fordham & Minot, ; Špinka & Algers, ; Das et al ., ; Dalezsczyk, ), we found that suckling bout duration and frequency decreased with increasing age of the foal in all three observed zebra species. However, in several ungulate species (cattle, impala Aepyceros melampus , Sumatran rhinoceros Dicerorhinus sumatrensis ), suckling bout duration is not affected by the age of the young (Lewandrowski & Hurnik, ; Mooring & Rubin, ; Plair, Reinhart & Roth, ) or even increased with an increasing age of the young (eland Taurotragus oryx ; Underwood, ; common hippopotamus Hippopotamus amphibius ; Pluháček & Bartošová, ). Therefore, we suggest that suckling bout duration seems to be better indicator of offspring needs than suckling frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Both calves were weighed daily starting the day after they were born, and the first year of weight data for both calves has been published in detail [Plair et al, ]. Daily body weights continued to be recorded for the female calf throughout the study.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous records reveal that the Sumatran rhinos mainly occur in coastal swamp forest, lowland, and mountain forest (van Strien 1985;Pusparini et al 2015). According to Plair et al (2011), the Sumatran rhino is a solitary species. However, this species could occasionally be found in a small group consisting of two or more individuals (van Strien 1985;Plair et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…According to Plair et al (2011), the Sumatran rhino is a solitary species. However, this species could occasionally be found in a small group consisting of two or more individuals (van Strien 1985;Plair et al 2011). The Sumatran rhinos appear to exhibit habitat preferences influenced by food abundance, topography, the source of minerals and water, and human presence (van Strien 1974;van Strien 1985;Pusparini et al 2015;Kretzschmar et al 2016).…”
Section: Introductionmentioning
confidence: 99%